Atomic spectrometry update. Environmental analysis - Butler, Owen T.; Cook, Jennifer M.; Davidson, Christine M.; Harrington, Chris F.; Miles, Douglas L. (Journal of analytical atomic spectrometry, 2009)
This is the twenty-forth annual review published in JAAS of the application of atomic spectrometry to the chemical analysis of environmental samples. This Update refers to papers published approximately between September 2007 and August 2008. In the analysis of air, work is focused on the need to collect and characterise ultrafines, i.e. particles below 100 nm in size, and such research is being facilitated through the development of air sampler technologies for subsequent off-line analysis of particles and aerosol mass spectrometric techniques for real-time measurements. In the analysis of water elemental speciation and development of vapour generation techniques for metalloid species continue to attract attention. Data quality and metrological issues are receiving renewed interest in part due to an increase in water quality regulations. In the field of soil and plant analysis, elemental fraction and speciation protocols based upon sequential extraction procedures, chromatographic separation procedures and synchrotron radiation X-ray techniques continue to be utilized and developed. As noted in previous Updates, laser ablation continues to go from strength to strength in being adopted as a solid sampling tool in geochemical analysis. Work continues to be focused on the production, characterization and certification of new geological reference materials. Feedback on this review is most welcome and the lead author can be contacted using the email address provided. Alternatively, readers are welcome to complete the on-line questionnaire at http://www.asureviews.org.